Platelet Aging In Vivo Is Associated with Activation of Apoptotic Pathways: Studies in a Model of Suppressed Thrombopoiesis in Dogs - Pereira, Jaime; Soto, Mónica; Palomo, Iván; Ocqueteau, Mauricio; Coetzee, Lindi-Marie; Astudillo, Smiljan; Aranda, Eduardo; Mezzano, Diego (Thrombosis and Haemostasis, 2002)
The mechanism(s) involved in the clearance of senescent platelets are largely unknown. We have recently demonstrated that platelet aging in vivo is associated with loss of membrane phospholipid asymmetry, a universal phenomenon in cells undergoing apoptosis. Thus, we postulated that senescent platelets may exhibit programmed cell death changes, which may trigger their removal from circulation. Since platelets contain the apoptosis machinery as well as mitochondria, a key organelle in the regulation of apoptosis, we studied the appearance of apoptotic-like changes during platelet aging in vivo. To investigate this, we assessed changes in mitochondrial membrane potential (Δψ) in circulating canine platelets during decline in platelet count after suppression of thrombopoiesis by estradiol injection, a validated model to obtain circulating platelets of increasing mean age. Phosphatidylserine (PS) exposure was determined by flow cytometry by binding of FITC-labeled annexin V. Mitochondrial Δψ was studied with the cationic lipophilic dye DIOC6 (3) and the J-aggregate-forming cation JC-1 and analysis by flow cytometry. The proportion of platelets with exposed PS rose significantly with age, from 2.88% before to 6.7%, 8 days after estradiol injection. By flow cytometry it was demonstrated a significant decreased in DIOC6 (3) fluorescence (median fluorescence intensity 791 ± 98 vs 567 ± 102 day 0 vs day 8 post injection of estradiol, respectively; n: 11; p <0.01), consistent with mitochondrial Δψ collapse. JC-1 has the unique property of forming J-aggregates under high mitochondrial Δψ (red fluorescence, FL2) whereas the monomeric form fluoresces in green (FL1). Aged platelets in vivo, loaded with JC-1, exhibited a significant increase in FL1/FL2 ratio (2.5 ± 1.7 vs 4.7 ± 1.6, day 0 vs day 8 post injection of estradiol, respectively; n: 13; p <0.05), confirming the mitochondrial Δψ alteration.The results show that platelet aging in vivo is associated with a decrease in mitochondrial Δψ and PS exposure. In conclusion, our data provide for the first time, evidence that platelet senescence is associated with changes characteristics of apoptosis, which may promote their removal from circulation.
Keywords: Platelet aging; apoptosis; mitochondria; platelet removal